Hardware testing on electro-mechanical system - Tan, Dijon Zheng Wu (2018)
The only marine transportation is by boats, ships and vessels and they all share a common thing which is the electrical motor to provide thrust and maneuvered direction for the vessel. Due to environmental concern, reducing pollution and preventing further damage to our mother nature, the tradition mechanical system of the propulsion engine is being transit into an electric hybrid type.